Endohedral fullerenes as standards for portable atomic clocks - Harding, R (2019)
Highly stable and accurate frequency sources underpin a wide range of modern technologies. For many applications, there is a need to develop clocks with low size, weight and power (SWaP). Significant effort has been expended in miniaturising existing atomic clock architectures, but the various limitations inherent to contemporary designs incentivise further exploration of novel architectures. Here, I investigate endohedral fullerenes as possible frequency references in future portable atomic clocks. Firstly, I detail the instrumentation developed to acquire the low-field data presented in this thesis. I then show that the endohedral fullerene 15N@C60 possesses a magnetic field-insensitive "clock transition" with fclock ≈ 38.6 MHz at a field Bclock ≈ 0.8 mT. This measurement is the first observation of a clock transition in a molecular spin system at room temperature, and it enables me to estimate the stability of an fullerene-based clock. The predicted performance is very poor, and I discuss potential strategies to address this problem. I also investigate the hyperfine coupling as a function of pressure. The measured shift (dA/dP ≈ 3.5 × 10-4 Hz Pa-1) is too small to be a useful tunable parameter with which to offset the temperature coefficient of a fullerene-based atomic clock. However, it does ensure that such a clock would be reasonably insensitive to atmospheric pressure fluctuations. Using this datum I make the first experimental estimate of the compressibility of an isolated fullerene cage. On the basis of the research performed in this thesis, I believe that the outlook for fullerene-based frequency standards is poor. They are fundamentally limited by their low frequency clock transitions and broad linewidths relative to the atomic frequency standards used in contemporary portable atomic clocks. This is due to their small hyperfine interaction and the coupling between the electron spin and degrees of freedom that are absent in atomic systems.